2017
DOI: 10.1111/odi.12662
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload induces apoptosis of murine preosteoblast cells via ROS and inhibition of AKT pathway

Abstract: Iron overload can generate ROS in cells, inhibit AKT kinase and its downstream proteins activity, and subsequently initiate apoptotic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Firstly, we found that iron exposure resulted in a reduction of cell viability, induction of ROS, and increasing of apoptosis in a dose-dependent manner in 1.1B4 cells that have been previously reported in other types of cell line such as HH4, human hematopoietic cells/mesenchymal cells, MC3T3-E1 cells, and MG-63 cells through different mechanisms (Li et al, 2016;Lu et al, 2013;Doyard et al, 2012;Yang et al, 2017;Ke et al, 2017). Many reports have been demonstrated that iron overload lead to increasing intracellular ROS and caused cell damage, which is concomitant with our results.…”
Section: Discussionsupporting
confidence: 66%
“…Firstly, we found that iron exposure resulted in a reduction of cell viability, induction of ROS, and increasing of apoptosis in a dose-dependent manner in 1.1B4 cells that have been previously reported in other types of cell line such as HH4, human hematopoietic cells/mesenchymal cells, MC3T3-E1 cells, and MG-63 cells through different mechanisms (Li et al, 2016;Lu et al, 2013;Doyard et al, 2012;Yang et al, 2017;Ke et al, 2017). Many reports have been demonstrated that iron overload lead to increasing intracellular ROS and caused cell damage, which is concomitant with our results.…”
Section: Discussionsupporting
confidence: 66%
“…Caspase-3 is widely recognized as a pro-apoptosis factor [22]. Meanwhile, AKT signaling pathway is closely associated with cell growth [23,24]. In the current study, we found the protein content of cleaved caspase-3 was upregulated in miR-338-5p mimic transfected cells.…”
Section: Mir-338-5p Overexpression Suppressed the Growth And Invasionsupporting
confidence: 49%
“…Studies in vitro and in vivo have indicated that iron overload induces differentiation of osteoclasts and inhibits proliferation of osteoblasts by catalyzing the generation of ROS (He et al, ; Lu et al, ). In addition, our previous study shows that iron overload induces apoptosis of murine preosteoblast cells via ROS and inhibition of the AKT pathway (Ke et al, ). Periodontal disease patients experience a periodontal iron overload state, which may inhibit the growth of osteoblasts in the alveolar bone.…”
Section: Discussionmentioning
confidence: 96%